Brown Adipocyte ADRB3 Mediates Cardioprotection via Suppressing Exosomal iNOS. Issue 2 (17th June 2022) - Lin, Jing-Rong; Ding, Li-Li-Qiang; Xu, Lian; Huang, Jun; Zhang, Ze-Bei; Chen, Xiao-Hui; Cheng, Yu-Wen; Ruan, Cheng-Chao; Gao, Ping-Jin
Abstract : Background: The ADRB3 (β3-adrenergic receptors), which is predominantly expressed in brown adipose tissue (BAT), can activate BAT and improve metabolic health. Previous studies indicate that the endocrine function of BAT is associated with cardiac homeostasis and diseases. Here, we investigate the role of ADRB3 activation-mediated BAT function in cardiac remodeling. Methods: BKO (brown adipocyte-specific ADRB3 knockout) and littermate control mice were subjected to Ang II (angiotensin II) for 28 days. Exosomes from ADRB3 antagonist SR59230A (SR-exo) or agonist mirabegron (MR-exo) treated brown adipocytes were intravenously injected to Ang II–infused mice. Results: BKO markedly accelerated cardiac hypertrophy and fibrosis compared with control mice after Ang II infusion. In vitro, ADRB3 KO rather than control brown adipocytes aggravated expression of fibrotic genes in cardiac fibroblasts, and this difference was not detected after exosome inhibitor treatment. Consistently, BKO brown adipocyte-derived exosomes accelerated Ang II–induced cardiac fibroblast dysfunction compared with control exosomes. Furthermore, SR-exo significantly aggravated Ang II–induced cardiac remodeling, whereas MR-exo attenuated cardiac dysfunction. Mechanistically, ADRB3 KO or SR59230A treatment in brown adipocytes resulted an increase of iNOS (inducible nitric oxide synthase) in exosomes. Knockdown of iNOS in brown adipocytes reversed SR-exo-aggravated cardiac remodeling. Conclusions: Our data illustrated a new endocrine pattern of BAT in regulating cardiac remodeling, suggesting that activation of ADRB3 in brown adipocytes offers cardiac protection through suppressing exosomal iNOS.